The Umbrella man and other stories - Dahl, Roald (New York : Speak, 2000)
Thirteen stories, selected for teenagers, from Dahl's adult writings, including "The Great Automatic Grammatizator," "Mrs. Bixby and the Colonel's Coat," and "Vengeance is Mine Inc."
Great automatic grammatizator -- Mrs. Bixby and the Colonel's coat -- Butler -- Man from the south -- Landlady -- Parson's pleasure -- Umbrella man -- Katina -- Way up to Heaven -- Royal jelly -- Vengeance is mine Inc. -- Taste -- Neck.
All Ages.
Keywords: Short stories, English; Short stories; Short stories